HUBUNGAN POLA MAKAN DENGAN KEJADIAN DIABETES MELLITUS DI RSUD KABUPATEN TAPANULI SELATAN - Ritonga, Nefonafratilova (Universitas Aufa Royhan, 2019)
Diabetes mellitus is a chronic metabolic disorder due to the pancreas not producing enough insulin or the body cannot use insulin produced effectively. According to Riskesdas 2018, the prevalence of people with diabetes mellitus in Indonesia increased from 6.9% in 2013 to 8.5% in 2018. This number increased from the previous year. The purpose of this study was to determine the relationship of eating patterns with the incidence of diabetes mellitus in South Tapanuli District Hospital. The research method used was analytic observation with a case control design with a control group. The sample in this study amounted to 38 case groups and 38 control groups. The data obtained were processed using the Chi Square test. The results showed a relationship between diet and the incidence of diabetes mellitus in South Tapanuli District Hospital. Based on the Chi Square statistical test results obtained p-value = 0,000 <0.005. The conclusion in this study there is a relationship of eating patterns with the incidence of diabetes mellitus in South Tapanuli District Hospital. Suggestions of this research can be used as a new source in increasing the knowledge of people with diabetes mellitus.